Exploratory factor and reliability analysis of entrepreneurial mindset instrument - Aryati Abd Rahman,; Sheerad Sahid,; Ahmad Zamri Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Entrepreneurial Mindset (EM) helps undergraduate students in public universities in Malaysia to identify problems or opportunities and to fi nd creative solutions in order to improve the situation in their personal life after graduation. Nevertheless, there is insuffi cient knowledge of the EM dimensions among undergraduate students at public universities in Malaysia. Therefore, this research examines the reliability and validity of the EM measurement scale among undergraduate students in Malaysian public universities. A self-administered survey questionnaire was used. The sample comprises 145 selected respondents, regularly randomized from undergraduate students at public universities in Malaysia. To measure the EM dimension, the items developed include the components of students’ prior knowledge, self-effi cacy, family background, and environment, comprising 41 items. Data were assessed employing exploratory factor analysis (EFA) via Statistical Package for the Social Sciences (SPSS) software. EM explains more than 60% of the variance in the relationship between items. The alpha value obtained from Cronbach is .90 over .60, which shows high reliability. All of the items in question examine the ending sustained due to the loading factor above .60 (students’ prior knowledge: 12 items; self-effi cacy: 6 items; family background: 9 items; and environment: 12 items). Four-factor components of entrepreneurship mindset constructs are already confi rmed. Due to the study, which confi rms the main construct on the importance of an EM, well-known graduates certainly benefi t as the group’s major target need. This study can help raise awareness and the importance of EM among students at public universities in the implemented program.